Glioblastoma with oligodendroglioma component in a ewe. (July 2016) - Pintus, Davide; Marruchella, Giuseppe; Masia, Mariangela; Maestrale, Caterina; Cancedda, Maria Giovanna; Contu, Claudia; Macciocu, Simona; Ligios, Ciriaco
Herein we describe a glioblastoma partially occupying the telencephalic portion of the left cerebral hemisphere of a Sardinian (syn. Sarda) breed ewe. Microscopically, the mass consisted of a pleomorphic spindle-shaped cell component organized as bundles and numerous small areas of round cells displaying an oligodendroglioma-like aspect. A high number of mitotic figures, large areas of necrosis surrounded by pseudopalisading glial cells, and multiple foci of dystrophic mineralization were also observed. The neoplasm was highly vascularized with glomerular vascular proliferation. Immunohistochemically, neoplastic cells proved to be strongly positive for nestin, vimentin, and olig-2, whereas they were invariably negative for synaptophysin. Few neoplastic cells and reactive astrocytes, mainly located at the edge of necrotic foci, proved to be positive for glial fibrillary acidic protein, whereas glomerular vascular proliferation was clearly positive for factor VIII and vascular endothelial growth factor. Gene sequencing analysis demonstrated homozygous p53 tumor suppressor gene ( TP53 ) point mutations in the DNA-binding domain located in exon 8. The presence of round cells immunoreactive for olig-2 demonstrated that this tumor is a glioblastoma with oligodendroglioma component. Our pathologic, immunohistochemical, and molecular findings largely overlap those previously reported in humans and dogs.